A phase 1 trial of the oral DNA methyltransferase inhibitor CC‐486 and the histone deacetylase inhibitor romidepsin in advanced solid tumors. Issue 16 (23rd April 2019) - Gaillard, Stéphanie L.; Zahurak, Marianna; Sharma, Anup; Durham, Jennifer N.; Reiss, Kim A.; Sartorius‐Mergenthaler, Susan; Downs, Melinda; Anders, Nicole M.; Ahuja, Nita; Rudek, Michelle A.; Azad, Nilofer
Abstract : Background: Epigenetic abnormalities are manifold in all solid tumors and include changes in chromatin configuration and DNA methylation. The authors designed a phase 1 study to evaluate the oral DNA methyltransferase inhibitor CC‐486 combined with the histone deacetylase inhibitor romidepsin in advanced solid tumors with dose expansion to further evaluate pharmacodynamics and possible clinical benefit of the recommended phase 2 dose (RP2D). Methods: This was a phase 1 study with a 3 + 3 dose‐escalation design and an expansion phase for patients with virally mediated cancers. The disease control rate (DCR) was the primary outcome for the expansion cohort. Correlative studies included long interspersed nucleotide element 1 (LINE‐1) methylation and drug exposure in blood samples (clinicaltrials.gov identifier NCT01537744). Results: Fourteen patients were enrolled in the dose‐escalation portion at 3 dose levels. Three patients experienced dose‐limiting toxicities; the RP2D was oral CC‐486 300 mg daily on days 1 through 14 and romidepsin 8 mg/m 2 on days 8 and 15. Because of slow accrual into the expansion phase, the trial was closed after 4 patients enrolled. Common toxicities of the combination included nausea (83.3%), anorexia (72.2%), fatigue (61.1%), and constipation (55.6%). There were 12 patients evaluable for response, 5 with stable disease, of whom 2 received >4 cycles; there were no responses. Exposure to CC‐486 and romidepsin was consistent with prior data. LINE‐1 methylation on C1D8 was significantly reduced (mean, −6.23; 95% CI, −12.23, −0.24; P  = .04). Conclusions: Although, at the RP2D, the combination of CC‐486 and romidepsin was tolerable, no significant anticancer activity was observed. Significant demethylation in post‐treatment circulating tumor DNA and biopsies provided proof of target acquisition. Abstract : The combination of CC‐486 and romidepsin is safe and tolerable; however, although pharmacodynamic data confirm on‐target effects, no significant anticancer activity is observed. Further development in combination with other antineoplastic therapies may be feasible.